A virus-like particle-based anti-nerve growth factor vaccine reduces inflammatory hyperalgesia: potential long-term therapy for chronic pain. - Röhn, T; Ralvenius, W; Paul, J; Borter, P; Hernandez, M; Witschi, R; Grest, P; Zeilhofer, H; Bachmann, M; Jennings, G (2011)
Chronic pain resulting from inflammatory and neuropathic disorders causes considerable economic and social burden. For a substantial proportion of patients, conventional drug treatments do not provide adequate pain relief. Consequently, novel approaches to pain management, involving alternative targets and new therapeutic modalities compatible with chronic use, are being sought. Nerve growth factor (NGF) is a major mediator of chronic pain. Clinical testing of NGF antagonists is ongoing, and clinical proof of concept has been established with a neutralizing mAb. Active immunization, with the goal of inducing therapeutically effective neutralizing autoreactive Abs, is recognized as a potential treatment option for chronic diseases. We have sought to determine if such a strategy could be applied to chronic pain by targeting NGF with a virus-like particle (VLP)-based vaccine. A vaccine comprising recombinant murine NGF conjugated to VLPs from the bacteriophage Qβ (NGFQβ) was produced. Immunization of mice with NGFQβ induced anti-NGF-specific IgG Abs capable of neutralizing NGF. Titers could be sustained over 1 y by periodic immunization but declined in the absence of boosting. Vaccination with NGFQβ substantially reduced hyperalgesia in collagen-induced arthritis or postinjection of zymosan A, two models of inflammatory pain. Long-term NGFQβ immunization did not change sensory or sympathetic innervation patterns or induce cholinergic deficits in the forebrain, nor did it interfere with blood-brain barrier integrity. Thus, autovaccination targeting NGF using a VLP-based approach may represent a novel modality for the treatment of chronic pain.